Influence of the season on nutritional and metabolic indicators of grazing cattle in the North of Mexico - Reyes, Osvaldo; Murillo, M.; Herera, Esperanza; Guti?rrez, E.; Su?rez, A. S.; Cerrillo, Andrea (Cuban Journal of Agricultural Science, 2012)
In grazing cattle, the nutritive quality, digestion and ruminal fermentation of the diet, blood glucose levels (GLU), urea nitrogen (UN) and non-sterified fatty acids (NSFA) were evaluated during the dry and rainy seasons. An analysis of variance according to a complete random block designs (CRBD) and with successive measurements was applied. Dry matter intake (DMC), organic matter intake (OMC), digestible energy (DEC), metabolizable energy (MEC), passage rate (Kp), and mean ruminal retention time of the diet were affected by the season of the year (P < 0.05). The crude protein (CP) and the effective protein degradation (EPD) of the diet, as well as the concentrations of ruminal ammonia nitrogen (N-NH3) and UN were higher in the rainy than in the dry season (P < 0.01). The contents of neutral detergent fiber (NDF) and the effective NDF degradation were also different between both periods of the year (P < 0.01). Similarly, the concentrations of acetic, propionic and butyric acids differed between seasons (P < 0.01). GLU concentrations were higher in the rainy season compared to the dry season (P < 0.01), while NSFA were higher during the latter (P < 0.05). Nutrient deficiencies recorded suggest the need of feeding supplementation for the animals, mainly protein and energy, during the dry season. Key words: cattle, degradation, glucose, urea-nitrogen, NSFA